Hassan al-Turabi’s Discourse on the Arts: Conservative Prohibition and Cautious Permission (American Journal of Islam and Society, 2015)
In Islam, God’s wondrous creativity is reflected in the unity of designin the widest diversity and beauty of the cosmos. For someMuslims, Islamic art expresses this natural beauty as well as themiracles of God’s creation related in the Qur’an and the prophetictraditions (aḥādīth). This article focuses on Hassan al-Turabi’sperceptions of the arts and the aura of conservative prohibitionand cautious permission that surrounds them. For him, the Islamicattitude toward the arts and aesthetics is determined by monotheism(tawḥīd), which entails one’s absolute belief in God’s onenessand the abjuration of anything that might compete with it or withHis omnipotence. God has created in beauty a dualistic nature:guidance (belief and faith) and temptation (seduction and aberration)for humanity.